CPFP: a central proteomics facilities pipeline. - Trudgian, D; Thomas, B; McGowan, S; Kessler, B; Salek, M; Acuto, O (2010)
UNLABELLED: The central proteomics facilities pipeline (CPFP) provides identification, validation, and quantitation of peptides and proteins from LC-MS/MS datasets through an easy to use web interface. It is the first analysis pipeline targeted specifically at the needs of proteomics core facilities, reducing the data analysis load on staff, and allowing facility clients to easily access and work with their data. Identification of peptides is performed using multiple search engines, their output combined and validated using state-of-the-art techniques for improved results. Cluster execution of jobs allows analysis capacity to be increased easily as demand grows. AVAILABILITY: Released under the Common Development and Distribution License at http://cpfp.sourceforge.net/. Demonstration available at https://cpfp-master.molbiol.ox.ac.uk/cpfp_demo.